Investigating the Role of Quercetin in Increasing the Rate of Cisplatin-Induced Apoptosis Via the NF-κB Pathway in MG-63 Cancer Cells - Ahmadi, Mehran; Valizadeh, Amir; Bazavar, Mohammadreza; Yousefi, Bahman (Drug Research, 2022)
Introduction Numerous studies suggest that the co-treatment of chemotherapeutic agents with flavonoids such as Quercetin (Que) may enhance tumor cells’ susceptibility to these agents. Hence, in the current study, we investigated Que’s role in combination with Cisplatin to promote cell apoptosis by focusing on the NF-κB signaling pathway in the osteosarcoma cell lines.Methods The Que, Cisplatin, and their combination’s general cytotoxicity effects were evaluated using an MTT assay for 72 hrs. The protein expression levels of NF-κB were detected by an enzyme-linked immunosorbent assay (ELISA) Kit. Flow cytometry was used to evaluate cell apoptosis.Results Que considerably elevated the cytotoxicity of Cisplatin (P<0.05). Que also dramatically down-regulated the expression levels of NF-κB in MG-63 cells compared to mono-treatment (P<0.05). Besides, Que promotes cisplatin-induced apoptosis in MG-63 cells.Conclusion Our study’s findings provide an exact point in the field of adjuvant therapy in osteosarcoma. In other words, this study could provide new insights into a better understanding of the role of Que in elevating cisplatin-induced apoptosis with NF-κB down-regulation.
Keywords: Osteosarcoma; Cisplatin; Quercetin; Apoptosis; NF-κB